Coopetition in for-profit and non-profit organizations - micro level = Koopetycji w organizacjach for-profit i non-profit - poziom mikro - Moczulska, Marta; Seiler, Bartosz; Stankiewicz, Janina (Zielona Góra: Faculty of Economics and Management Press)
A situation in which appears at the same time a competition and cooperation between the subjects is defined as a coopetition. First of all it is considered at the mezo level ? between the companies, but it can be analysed at the micro level ? inside the organization. In the second case, it concerns shaping the relations among the employers which compete one with another and at the same time they cooperate. Among the organizations where the coopetion can be analysed we distinguish two types - for profit and non profit.
Keywords: organizacje for-profit; organizacje non profit; współdziałanie; konkurencja; kompetycja; for-profit organizations; non profit organization; cooperation; competition; coopetition